Effectiveness of dry needling in the treatment of neck pain and disabilityassociated with myofascial trigger points - (:unkn) unknown (My University, 2021)
Objective: The aim of this study is to evaluate the effectiveness of dry needling (DN) with fast-in and fast-out technique for myofascialtrigger points (MTrPs) in the upper trapezius muscle associated with neck pain.Patients and Methods: Patients aged 18-70 years, who have had neck pain at least one active MTrP in the upper trapezius muscletreated with DN, were included in the study. Pain and disability were assessed with Numeric Rating Scale (NRS) and Neck DisabilityIndex (NDI) before treatment (T0), after first session (T1) and after last session (T2). Number of MTrPs where DN was performedand the number of DN sessions were recorded. Patients were evaluated based on the minimal clinically important change (MCIC)scores for NRS and NDI.Results: A total of 76 patients (Female: 67, Male: 9) were included in the study. Median number of DN sessions was 3 and median ofMTrPs that DN performed was 4. Both NRS and NDI showed significant improvement at T1 and T2. More than 90% of patients hadMCIC at T1 and T2.Conclusion: Dry needling with fast-in and fast-out technique is effective for pain and disability management in patients with neckpain due to MTrPs.